9/11 - Hanlon, James; Klug, Rob; Naudet, Gédéon; Naudet, Jules (United States, 2002)
On the morning of September 11, 2001, French filmmaker brothers Jules and Gedeon Naudet were working on a documentary about a rookie New York City firefighter. Hearing a roar in the sky, Jules turned his camera upward--just in time to film the only existing image of the first plane crashing into the World Trade Center. With cameras rolling, the Naudets followed NYC firefighters into the heart of what would be known as Ground Zero. What emerged is a powerful visual document and a stirring tribute to the firefighters at WTC.
Off-air recorded from the Hungarian Television MTV. Some original English language sound is heard throughout the film. Also on the tape are 4 other off-air recordings relating to 9/11 and its legacy in the USA, including the documentary titled "Flight 93".
Duration: 01:53:00
Keywords: Documentary films